Processing of syllable stress is functionally different from phoneme processing and does not profit from literacy acquisition - Schild, Ulrike; Becker, Angelika B. C.; Friedrich, Claudia K. (Frontiers in Psychology, 2014)
Speech is characterized by phonemes and prosody. Neurocognitive evidence supports the separate processing of each type of information. Therefore, one might suggest individual development of both pathways. In this study, we examine literacy acquisition in middle childhood. Children become aware of the phonemes in speech at that time and refine phoneme processing when they acquire an alphabetic writing system. We test whether an enhanced sensitivity to phonemes in middle childhood extends to other aspects of the speech signal, such as prosody. To investigate prosodic processing, we used stress priming. Spoken stressed and unstressed syllables (primes) preceded spoken German words with stress on the first syllable (targets). We orthogonally varied stress overlap and phoneme overlap between the primes and onsets of the targets. Lexical decisions and Event-Related Potentials (ERPs) for the targets were obtained for pre-reading preschoolers, reading pupils and adults. The behavioral and ERP results were largely comparable across all groups. The fastest responses were observed when the first syllable of the target word shared stress and phonemes with the preceding prime. ERP stress priming and ERP phoneme priming started 200 ms after the target word onset. Bilateral ERP stress priming was characterized by enhanced ERP amplitudes for stress overlap. Left-lateralized ERP phoneme priming replicates previously observed reduced ERP amplitudes for phoneme overlap. Groups differed in the strength of the behavioral phoneme priming and in the late ERP phoneme priming effect. The present results show that enhanced phonological processing in middle childhood is restricted to phonemes and does not extend to prosody. These results are indicative of two parallel processing systems for phonemes and prosody that might follow different developmental trajectories in middle childhood as a function of alphabetic literacy.